Innovative Adoption of The Use of Biosaka Elisator in Rice Cultivation in Aceh - Nurhijjah, Nurhijjah; Romano, Romano; Fajri, Fajri (MSJ : Majority Science Journal, 2024)
The importance of innovation in the agricultural sector to increase the productivity and welfare of farmers, especially in the use of environmentally friendly technologies such as Biosaka on rice plants. Although Biosaka offers a wide range of benefits, the adoption of this innovation still faces challenges, especially related to the characteristics of farmers, the nature of the innovation, and the effectiveness of extension. The purpose of this study is to analyze the influence of farmer characteristics, innovation nature, and counseling on the adoption of innovation in the use of Biosaka on rice plants. This study uses a quantitative method with a survey approach that involves sampling from one population and using questionnaires as a data collection tool. The research was conducted in three clusters in Pidie, East Aceh and West Aceh with a population of 50 people in each cluster so that a total of 150 respondents. The results showed that the characteristics of farmers and the nature of innovation had a significant effect on the adoption of innovations in the use of Biosaka. Farmers who have experience, education, and a certain age tend to be more receptive to the use of Biosaka because they feel the benefits and usefulness of the innovation. However, counseling on Biosaka did not have a significant effect on the adoption of this innovation, showing that the counseling carried out was still less effective in increasing farmers' understanding and interest. The implication of this study is the need to improve the quality and intensity of extension programs to better target the characteristics of farmers and increase their understanding of the benefits of Biosaka.